Rendahnya Kontribusi Orang Tua dalam Meningkatkan Pendidikan Anak - Luthfiatunnisa, Farah Fauziah; Nurfadillah, Yoane Siti; Maghfira, Rhaudya Zihan Esa; v, Anggista Dwiana; Safitri, Awalia; Prihantini, Prihantini (Indo-MathEdu Intellectuals Journal, 2025)
The low contribution of parents in improving children's education has an impact on the academic, social, and emotional aspects of children. This study aims to identify the factors that cause low parental involvement as well as efforts that can be made to improve the role of parents in education. This study uses a qualitative descriptive method. Data collection techniques through observation of interactions between parents and children in the school environment. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. The research findings indicate that internal factors such as time constraints and understanding of education, as well as external factors such as culture and social pressure, are the main obstacles. Therefore, parent education programs, flexibility in school activities, and more effective communication between parents and schools are needed to increase parental involvement.